Lenticulorhexis Versus Traditional SMILE - Mohamed, M.D, Ahmed G. E.; Salem, M.D, Mohsen Emadeldin; Ahmed Hassanein M.D; Fikry, M.D, Ramy Riad (Journal of Neonatal Surgery, 2025)
Background: Surgical treatment modalities for refractive errors include Laser Assisted In-situ Keratomileusis (LASIK), radial keratotomy, intrastromal corneal ring segments, lenticular extraction, etc. Later, Femtosecond Lenticule Extraction (FLEx) was designed for the treatment of severe myopic patients. With the arrival of the Visumax femtosecond laser and technique refinement by creating 2-3 mm small incisions, small incision lenticule extraction (SMILE) became an in- creasingly popular refractive surgery, which was approved in 2012 by the food and drug administration (FDA), and since then there have been numerous international research were conducted on determining its efficacy and visual outcomes. Aim of Study: To evaluate the effectiveness of two different approaches to the SMILE technique (traditional verses lenti- culerrhexis) in myopic patients. Material and Methods: This study included 60 eyes (n=31 patients) that underwent SMILE for correction of myopia between July 2016 and July 2019. The subjects' eyes were randomly divided into two groups of 30 eyes. Group A eyes underwent lenticulerrhexis (CCL), and group B underwent the conventional myopic correction procedure. A comprehen- sive preoperative examination was done for all subjects, which included slit lamp examination, Pentacam imaging, measuring intraocular pressure (IOP), and uncorrected/ corrected distance visual acuity measurements were recorded. Postoperative follow-up was performed on day one and three-months. Primary Outcomes included Bowman's layer micro-distortions and contrast and sensitivity test, while secondary outcomes included corrected and uncorrected distance visual acuity, lenticule extraction duration, manifest refraction, and adverse events. Results: No significance (p=0.52) was demonstrated between group A and B regarding mean pre-operative spherical equivalent (SE), the SE was –4.75 for group A and –4.78 in group B. Bowman's Layer distortions were 3.73, 6.6, and 3.00, 4.73 in group A and B at day one and three-months postoperatively, respectively (p=0.06). Mean contrast and sensitivity was 281, 277, and 317, 320 in groups A and B respectively, at day one and three-months postoperatively, respectively (p=0.38, p=0.52 - Day one and three months postop.). A UDVA of 0.8 or better was demonstrated in 96.7% (29 of 30) for group A and 86.7% (26 of 30) of group B, and no difference between both groups (p=0.16). Sphere equiva- lence mean was –0.16 diopters for group A and –0.27 diopters for group B (p=0.41). The mean length of time of lenticule extraction was 78.4 seconds (range: 59.5 to 124.5 seconds) in group A and 74.3 seconds (range: 52 to 102 seconds) in the conventional group. Conclusion: The CCL technique is an excellent, repro- ducible, less manipulative, and efficient technique of SMILE surgery, that may result in better early corneal healing and visual outcomes compared to the conventional SMILE tech- nique. It is a promising technique that deserve further research and evaluation.